Pengaruh Persepsi Mahasiswa Tentang Ketrampilan Mengajar Dosen Dan Komunikasi Antara Dosen Dengan Mahasiswa Terhadap Motivasi Belajar Statistika Perusahaan 1 - Saputri, Ika Ayu (2016)
The purpose of research is to determine: 1) Effects of student perceptions of faculty teaching skills on motivation to learn statistical companies 1; 2) Effect of communication between faculty and students on motivation to learn statistical companies 1; 3) Effects of student perceptions of faculty teaching skills and communication between faculty and students on motivation to learn statistics firm 1. This type of research is quantitative associative. The population in the study were all students of Universitas Muhammadiyah Surakarta accounting force in 2014, amounting to 237 students with 142 samples taken student with Proportionate Random Sampling technique. Data collection techniques by using questionnaires that have been tested valididtas test and reliability test. Technical analysis of the data used is multiple linear regression, t test, F test, the relative contribution and effective contribution Based on the analysis and discussion can be concluded that: 1) there is significant relationship between student perception about teaching skill faculty motivation to learn statistics firm 1 by t test obtained t> t table, namely 6.134> 1.984 and significant value <0.05 is 0.000. 2) there was a significant effect of communication between faculty and students on motivation to learn statistics firm 1 by t test obtained t> t table, namely 3.435> 1.984 and significant value <0.05 is 0.001. 3) No student prsepsi influence on faculty teaching skills and communication between faculty and students on motivation to learn statistics firm F 1 based test known Fhitung> Ftable is 48.549> 3.07 with significant value of 5%. The result of the calculation to the value of R2 obtained 41.1% of motivation to learn statistics firm 1 is influenced by students' perceptions of faculty teaching skills and communication between faculty and students, while the remaining 58.9% is influenced by other variables not examined in this study.